HUBUNGAN MANAJEMEN WAKTU DENGAN KEBIASAAN PROKRASTINASI PENYUSUNAN SKRIPSI MAHASISWA KEPERAWATAN ANGKATAN VIII STIKES BINA USADA BALI (Widyadari: Jurnal Pendidikan, 2018)
Time management plays a role in the completion of student academic tasks well. The inability of students in time management leads them to tend to delay doing their academic tasks. The delay in doing these academic tasks is called "academic procrastination". This behavior can give negative effect for student of course. Students who do procrastination will need more time to complete their studies than students who do not do procrastination. Procrastination can lead to a decrease in productivity that leads to lower individual quality and can cause stress, anxiety, and difficulty in concentrating. The purpose of this study to see whether time management affects the procrastination habits of nursing department STIKES Bina Usada Bali?s student class of 2014 in writing graduating paper and how much influence those variable given. Research design used cross sectional with quantitative approach. Data was collected through filling questionnaire of 70 nursing students in September 2017 in STIKES Bina Usada Bali. Data analysis including univariate and bivariate analysis with kendall?s tau correlation coefficient. Univariate analysis showed that most of the nursing students had the time management skill on high category 36 respondents (51,4%) and had average level of graduating paper writing procrastination around 34 respondents (48,6%). Bivariate analysis with Kendall?s Tau correlational value of    -0,233 showed that there was a weak relation with p value 0,03 was smaller than ? = 0,05 (p<0,05) meant that there was significant relation between time management skill and graduating paper procrastination level among nursing department of STIKES Bina Usada Bali?s students, class of 2014. Time management skill is necessary for students to reduce the tendency of graduating paper writing procrastination, when the time management skill is high, the level of graduating paper procrastination becomes lower, in order to encourage nursing students to graduate on time..